P1010EFFECTS OF SGLT2 INHIBITORS ON DIABETIC NEPHROPATHY: PODOCYTURIA ON FOCUS. (6th June 2020) - Ozkan, Serbay; Saygi, Halil İbrahim and Polat Korkmaz, Ozge and Durcan, Emre and Murt, Ahmet and Sahin, Serdar and Dincer, Mevlut Tamer and Bakir, Alev and Özkaya, Hande mefküre and Trabulus, Sinan and Seyahi, Nurhan and Güzel, Elif and Gönen, Mustafa Sait
Abstract: Background and Aims: Sodium-glucose co-transporter 2 (SGLT2) inhibitors which are a class of oral anti-diabetic drugs are being used in the treatment of type 2 diabetes (T2D). Basically these drugs reduce blood glucose by blocking glucose reabsorption of primary sodium-coupled glucose transporter in the proximal tubules. Diabetic nephropathy (DN) is a progressive disease with the pathology of glomerular filtration barrier damage and loss of podocytes. In this respect, podocyturia which is the case characterized with presence of podocytes in urine have recently been considered to be a candidate marker for glomerular damage. Therefore, we aimed to investigate effects of SGLT2 inhibitors on glomerulus through the evaluation of podocyturia in DN patients. Method: Our study population was composed of two T2D patient groups; one of which received SGLT2 inhibitor (SGLT2 group) and the other one is control which did not received. Patients with T2D for at least 5 years, diagnosed with DN and having microalbuminuria >30 mg/day, glomerular filtration rate (GFR) >60 ml/min and HbA1c< 8.5 were involved. In addition, all patients had received angiotensin converting enzyme inhibitor or angiotension receptor blocker for at least 6 months. Nephrologic parameters of patients were monitored before and 3 rd and 6 th month of follow up period. Patients' age, sex, diabetes duration and HbA1c value were obtained from medical charts. GFR was calculated using the abbreviated MDRD formula. Microalbuminuria was measured in 24 hour urine. Number of podocytes in the urine was determined by immunocytochemical staining of two different markers as podocalyxin (podx) and synaptopodin (synp). Statistical analyses were carried out using Statistical Package for the Social Sciences version (SPSS) 24.0 and statistical significance was set as p<0.05. Results: We evaluated a total of 29 patients (mean age: 57.59 ± 9.66). The number of patients for SGLT2 and control groups are 18 (mean age: 54.89 ± 7.73) and 11 (mean age: 62.00 ± 11.60) respectively. Between these two groups, there was no statistical difference with respect to durations of diabetes (p=0.875) and HbA1c (p=0.05) values except for age (p=0.023) in which control group is statistically higher than the SGLT receiving group. Among the patients receiving SGLT2 inhibitor, podocyturia and microalbuminuria (mca) levels in the 6 th month of follow up period were statistically lower than the initial ones [p=0.039 (synp), p=0.016 (podx) and p=0.011 (mca) respectively] while there was no statistical difference for creatinine clearance rate between the initial and follow up period (p:0.371 and ;p=0.111) (Figure-1 ). For control group, although podocyturia was significantly reduced in the 6 th month of follow up period [p=0.013 (synp) and p:0.005 (podx)], microalbuminuria (p=0.263) in addition to creatinine clearance (p:0.214; p=0.173) did not change significantly (p=0.263). Furthermore, while there was no significant difference for initial microalbuminuria level between the control and SGLT2 groups (p=0.353); in the 3 rd and 6 th month follow up period, microalbuminuria was significantly lower than the control group accordingly (p=0.011 and p=0.015 respectively). Conclusion: According to our preliminary results; patients receiving SGLT2 inhibitors had better microalbuminuria levels than the ones did not and this parameter was correlated with podocyturia. However, even though microalbuminuria of the control group did not change during the follow up period, podocyturia was found out as reduced in the 6 th month of follow up period. This discrepancy in the podocyturia level could be resulted from lower number of patients in control so that there is need for evaluation of more patients to emphasize podocyte protective effect of SGLT2 inhibitors.